Encyclopedia of modern U.S. military weapons - Laur, Timothy M. (Berkley Books, 1998)
An accessible encyclopedia of military weapons represents a collaboration with The Army, Navy, and Air Force Times, and covers each weapon system, its evolution, development, and combat experience.